2
$\begingroup$

The standard proof of the identity $\sin^2x + \cos^2x = 1$ (the one that is taught in schools) is as follows: from pythagoras theorem, we have (where $h$ is hypotenuse, $b$ is base and $p$ is perpendicular) $$h^2 = p^2 + b^2$$ dividing by $h^2$ on both sides: $$1 = \frac{p^2}{h^2}+\frac{b^2}{h^2}$$ since $\sin x = \frac ph$ and $\cos x = \frac bh$, $$1 = \sin^2x+\cos^2x$$

Are there any more innovative ways of proving this common identity?

$\endgroup$
  • 4
    $\begingroup$ It all boils down to the definition of sin and cos. Which one are you using? $\endgroup$ – lhf Apr 26 at 14:38
  • $\begingroup$ I bet there are dozens, depending on what you allow to be a given fact. $\endgroup$ – Marius S.L. Apr 26 at 14:38
  • 1
    $\begingroup$ I would guess $n+1$. $\endgroup$ – Michael Hoppe Apr 26 at 14:52
  • 1
    $\begingroup$ Cf. this question $\endgroup$ – J. W. Tanner Apr 26 at 15:06
6
$\begingroup$

Here's a couple of different methods:

Proof using the cosine angel sum formula:$$ 1=\cos(0) =\cos(x + (-x)) =\cos(x)\cos(-x) - \sin(x)\sin(-x) = \cos^2(x) + \sin^2(x) $$ Proof using differential equations: Recall the differential equation definitions of $\sin$ and $\cos$: They are the solutions to $f'' = - f$ with the appropriate initial conditions $f(0) = 0$, $f'(0) = 1$ for $\sin(x)$ and $f(0) = 1$, $f'(0) = 0$ for $\cos(x)$. Since solutions to differential equations are unique given the initial conditions, we immediately get $\sin'(x) = \cos(x)$ under this definition. Then:\begin{eqnarray} \frac{d}{dx} \left(\sin^2(x) + \cos^2(x)\right) &=& \frac{d}{dx} \left(\sin^2(x) + \left(\sin'(x)\right)^2\right)\\ &=& 2\sin(x)\sin'(x) + 2\sin'(x)\sin''(x)\\ &=& 2\sin(x)\sin'(x) +2\sin'(x)(-\sin(x)) = 0 \end{eqnarray} hence $\sin^2(x) + \cos^2(x)$ is constant, since its derivative is 0. Plugging in $x=0$ we see that it must equal 1.

Proof using Euler's formula: $$ \sin^2(x) + \cos^2(x) = \left(\cos x + i \sin x\right)\left(\cos x - i \sin x\right) =\left(\cos x + i \sin x\right)\left(\cos (-x) + i \sin (-x)\right)= e^{i x} e^{-i x} = 1 $$ Proof using Taylor series: Using the Taylor series:\begin{eqnarray} \sin(x) = \sum_{n=0}^\infty \frac{(-1)^n x^{2n+1}}{(2n+1)!}\\ \cos(x) = \sum_{n=0}^\infty \frac{(-1)^n x^{2n}}{(2n)!} \end{eqnarray} we have $$ \sin^2(x) = \left(\sum_{n=0}^\infty \frac{(-1)^n x^{2n+1}}{(2n+1)!}\right)^2 = \sum_{n=0}^\infty \sum_{m=0}^\infty \frac{(-1)^{n+m} x^{2n + 2m + 2}}{(2n+1)!(2m+1)!} = \sum_{k=0}^\infty x^{2k+2}(-1)^k \sum_{j=0}^k \frac{1}{(2j+1)!(2(k-j)+1)!}= \sum_{k=0}^\infty \frac{x^{2k+2}(-1)^k}{(2k+2)!}\sum_{j=0}^k \binom{2k+2}{2j+1} = -\sum_{k=1}^\infty \frac{x^{2k}(-1)^k}{(2k)!}\sum_{j=0}^{k-1} \binom{2k}{2j+1} $$ and $$ \cos^2(x) =\left(\sum_{n=0}^\infty \frac{(-1)^n x^{2n}}{(2n)!}\right)^2 = \sum_{n=0}^\infty \sum_{m=0}^\infty \frac{(-1)^{n+m} x^{2n + 2m}}{(2n)!(2m)!} = \sum_{k=0}^\infty x^{2k}(-1)^k \sum_{j=0}^k \frac{1}{(2j)!(2(k-j))!} = \sum_{k=0}^\infty \frac{x^{2k}(-1)^k}{(2k)!}\sum_{j=0}^k \binom{2k}{2j} = 1 + \sum_{k=1}^\infty \frac{x^{2k}(-1)^k}{(2k)!}\sum_{j=0}^k \binom{2k}{2j} $$ Adding these together:$$ \sin^2(x) + \cos^2(x) = 1+\sum_{k=1}^\infty\frac{x^{2k}(-1)^k}{(2k)!}\left(\sum_{j=0}^k \binom{2k}{2j}-\sum_{j=0}^{k-1} \binom{2k}{2j+1}\right)=1+\sum_{k=1}^\infty\frac{x^{2k}(-1)^k}{(2k)!}\left(\sum_{j=0}^{2k} (-1)^j\binom{2k}{j}\right) = 1+\sum_{k=1}^\infty\frac{x^{2k}(-1)^l}{(2k)!} (1 + (-1))^{2k} = 1 $$ We use the binomial theorem on the second last step.

Carlson's Theorem: Major overkill to use this one, but it still works. Notice $\cos(x)$, and $\sin(x)$ have exponential type 1. Thus $$ f(x) = \cos^2(\frac{\pi}{4}x) + \sin^2(\frac{\pi}{4}x) - 1 $$ has exponential type at most $\frac{\pi}{2} < \pi$. By inspection, you can see that $f(x) = 0$ for $x\in \mathbb{N}$. Hence Carlson's theorem implies $f(x) = 0$ identically.

| cite | improve this answer | |
$\endgroup$
  • 1
    $\begingroup$ It's called the "cosine angle sum" formula, although I'd argue the way it's used is pretty angelic. :) $\endgroup$ – Lieutenant Zipp Apr 26 at 18:29
3
$\begingroup$

Calculus

Let $f(x)=\sin^2x + \cos^2x$. Then $f'(x)=0$ and so $f$ is constant, $f(x)=f(0)=1$.

This proof depends on $\sin'=\cos$, $\cos'=-\sin$.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ (+1) Nice approach :) $\endgroup$ – Learning Apr 26 at 15:14
3
$\begingroup$

A few proofs I came up with are:

Proof 1: This uses real analysis. Let $f(x) = \sin^2x + \cos^2x \implies f'(x) = 2\sin x \cos x - 2\sin x \cos x = 0$. Thus, $f(x)$ is a constant function. To find the value of $f(x)$, it is sufficient to find $f(c)$, where c is any convenient constant (say 0). Therefore, $f(x) = f(0) = 1$

Proof 2: This uses Euler's representation of complex numbers. We can represent a complex number in the form $z = re^{ix}$, where $r$ is the modulus and $z$ is the argument. If we take the number $z = e^{ix} = \cos x + i\sin x$ (De Moivre's theorem), then $|z| = 1 = \sqrt{\cos^2x + \sin^2x} \implies \cos^2x + \sin^2x=1$.

| cite | improve this answer | |
$\endgroup$
3
$\begingroup$

One way is to use the complex definitions of sine and cosine. $$\sin\theta=\frac{e^{i\theta}-e^{-i\theta}}{2i} \\\cos\theta=\frac{e^{i\theta}+e^{-i\theta}}{2}$$ $$\begin{align*} \sin^{2}\theta + \cos^{2}\theta &= \Big( \frac{e^{i\theta}-e^{-i\theta}}{2i}\Big)^{2}+\Big(\frac{e^{i\theta}+e^{-i\theta}}{2} \Big)^{2} \\ &= -\frac{e^{2i\theta}-2e^{i\theta}e^{-i\theta}+e^{-2i\theta}}{4}+\frac{e^{2i\theta}+2e^{i\theta}e^{-i\theta}+e^{-2i\theta}}{4} \\ &=-\frac{e^{2i\theta}-2+e^{-2i\theta}}{4}+\frac{e^{2i\theta}+2+e^{-2i\theta}}{4} \\ &=\frac{4}{4} \\&=1\end{align*}$$

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

$$\left(\frac{e^{ix}+e^{-ix}}{2}\right)^2+\left(\frac{e^{ix}-e^{-ix}}{2i}\right)^2$$ $$=\frac{1}{4}\left[\left(e^{2ix}+2+e^{-2ix}\right)-\left(e^{2ix}+2+e^{-2ix}\right)\right]=\frac{4}{4}=1$$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ obtain expressions for $\sin(x)$ and $\cos(x)$ using a manipulation of Euler's formula $\endgroup$ – Henry Lee Apr 26 at 14:56
2
$\begingroup$

1) With identity $a^2-b^2= (a-b)(a+b)$,

$$\cos^2x+ \sin^2x = (\cos x-i\sin x)(\cos x+i\sin x)=e^{-i x}e^{i x}=1$$

2) With double angle identities,

$$\cos^2x+ \sin^2x =\frac12 (1+\cos 2 x)+\frac12(1-\cos 2x)=1$$

3) with half-angle subs $t= \tan\frac x2$,

$$\cos^2x+ \sin^2x =\left(\frac{1-t^2}{1+t^2}\right)^2 +\left(\frac{2t}{1+t^2}\right)^2 =\left(\frac{1+t^2}{1+t^2}\right)^2 =1$$

4) As an integral,

$$f(x)=\cos^2x+ \sin^2x =f(0) + \int_0^x f’(t)dt = 1+0=1$$

5) With $x=it $, apply $\sin(it)= i\sinh t$ and $\cos(it)=\cosh t$

$$\cos^2x+ \sin^2x = \cosh^2 t - \sinh^2 t = \left(\frac{e^t+e^{-t}}{2}\right)^2 -\left(\frac{e^t-e^{-t}}{2}\right)^2 =1$$

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

Special case of the addition theorems $$\sin(a+b)=\sin(a)\cos(b)+\sin(b)\cos(a)$$ and $$\cos(a+b)=\cos(a)\cos(b)-\sin(a)\sin(b)$$ by letting $a=-b=x$ in the second theorem. (The slickest prove of those theorems undoubtedly comes from Erhard Schmidt, see Proof of the angle sum identity for $\sin$.)

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ It's not clear how you're using the sine formula to get $\cos^2(x) + \sin^2(x) = 1$. (Letting $a=-b=x$ yields the trivial $\sin(0) = \sin(x)\cos(x) - \sin(x)\cos(x)$) $\endgroup$ – Dark Malthorp Apr 28 at 18:35
  • $\begingroup$ Only the theorem for $\cos$ is needed: $$1=\cos(0)=\cos(x)\cos(-x)-\sin(x)\sin(-x)=\cos^2(x)+\sin^2(x).$$ $\endgroup$ – Michael Hoppe Apr 29 at 7:50

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.